Concept of Moral Education According to KH. Hasyim Asy'Ari in the Book of Adabul 'Alim Wal-Muta'alim - Siti Rohmah (STIT Islamic Village Tangerang, 2020)
The purpose of this research is to find out and study the concept of moral education according to KH. Hasyim Asyari in the book adabul ‘alim wal muta’allim. This research is a study of character studies or individual biographical research which is a type of qualitative research with a textual approach. Data sources are relevant reference books following the issues discussed, Al-Qur'an and hadiths, especially KH. Hasyim Asy'ari in the book adabul ‘alim wal muta’allim. The data analysis technique uses deductive and inductive methods. This research shows that the concept of moral education according to KH Hasyim Asy'ari is very much needed in the world of education, which can then be accustomed to running it within the scope of family, school, relationships, and social society. Characteristics of KH. Hasyim Asy'ari in the book is guided by the Qur'an and the Hadith. KH. Hasyim Asy’ari, which emphasizes ethical values that have Sufistic breath. Moral Education which he emphasized, namely: morals to God and morals to fellow human beings. His concept made the development of a society of religious morality with individual coaching. With the aim that is expected to be able to realize a society of good character, noble and noble character.